Identification of Wavy Grained Red Sanders (Pterocarpus santalinus) at Nursery Stage - Rawat, M. S.; Uniyal, D. P. (Indian Forester, 1996)
Highly wavy grained wood of Red Sanders fetches fabulous prices in the export market, particularly Japan. While the straight grained or normal grained is sold at a very cheap rate. Hence, to increase the frequency of highly wavy grained trees it is necessary to multiply them for large scale plantations, directly or indirectly. A method has been suggested to identify the highly wavy grained plants at nursery stage.